Voltage-dependent calcium channels in the neurosecretory cells of cerebral ganglia of the mud crab, Scylla paramamosain. Issue 13 (5th September 2018) - Bao, Chenchang; Yang, Yanan; Huang, Huiyang; Ye, Haihui
Abstract : Voltage-dependent calcium channels (VDCCs) play a critical role in stimulus–secretion coupling in neurosecretory cells (NSCs). The crustacean cerebral ganglion plays a crucial role in neuromodulation and controls neuropeptide release. The present study used patch-clamp and Illumina sequencing techniques to investigate the potential features of VDCC in the cerebral ganglia of the mud crab ( Scylla paramamosain ). The electrophysiological characteristics of VDCC were analyzed in three types of NSCs with a patch clamp. The thresholds for activation of Ca 2+ channel current recorded from all the three types of NSCs were all above −40 mV, with peak amplitudes occurring around 0 mV. Therefore, it was concluded that the currents recorded in NSCs were mediated by high-voltage-activated Ca 2+ channels. Ca 2+ channel current densities in I type NSCs were significantly lower than those in II and III type NSCs. Four VDCC subunits derived from three transcripts were predicted from a transcriptome database of the cerebral ganglia. Among these transcripts, Ca v α1, Ca v β, and Ca v α2 / δ were predicted to encode 1674, 554, and 776 amino acids, respectively, and they shared conservative domains with VDCC subunits in other species. Overall, these findings provide an important basis for further studies on the neuroendocrine mechanisms in crustaceans. Abstract : Supplemental Digital Content is available in the text.